Serum Inflamma-miR Signature: A Biomarker of Myelodysplastic Syndrome? - Mariani, Marianna; Mattiucci, Domenico; Rossi, Elisa; Mari, Valeria; Masala, Erico; Giuliani, Angelica; Santini, Valeria; Olivieri, Fabiola; Marinelli Busilacchi, Elena; Mancini, Stefania; Olivieri, Attilio; Poloni, Antonella (Frontiers in Oncology, 2020)
Myelodysplastic Syndromes (MDS) are a heterogeneous group of clonal stem cell disorders that predominantly affect the elderly. They are characterized by ineffective hematopoiesis, peripheral blood cytopenias and an increased risk of developing acute myeloid leukemia. Chronic inflammation plays a crucial role in MDS pathogenesis and progression. Mounting evidence has been suggesting the potential diagnostic/prognostic value of circulating microRNAs (miRNAs) – short non-coding RNAs that are capable of modulating gene expression – in MDS and other hematologic malignancies. In this study, the serum expression of 14 miRNAs involved in the modulation of inflammation (inflamma-miRs) was determined in 68 MDS patients and 68 age-matched healthy donors to identify those having diagnostic/prognostic value. Compared to the healthy donors, patients had significantly lower miR-155 and miR-181a and significantly higher miR-19b levels. When patients were grouped according to the International Prognostic Scoring System (IPSS), those at lower risk showed significantly lower miR-21, -146a, -155, and -181a levels and significantly higher miR-19b levels. Notably, 2-year overall survival probability was significantly lower in patients with higher miR-21, -155, and -181a. Altogether, our data suggest that an MDS-specific circulating inflamma-miR signature could provide an innovative, non-invasive diagnostic and prognostic biomarker of these disorders.